2018
DOI: 10.1097/aap.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Low-Dose Dexamethasone Prolongs Interscalene Block Analgesia With Bupivacaine Compared With Systemic Dexamethasone

Abstract: This study was registered at Clinicaltrials.gov, identifier NCT02506660.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…24 Individual studies have had varied results (ISB and other blocks). Whereas some studies have concluded that perineural dexamethasone provides superior analgesia, 25,26 others have determined statistically significant but clinically insignificant differences, 27 and yet others have found no statistically significant differences between groups thereby concluding equivalence. 16,18,28 There are potential explanations for the contrasting results between these studies and our results identifying minimal differences.…”
Section: Discussionmentioning
confidence: 99%
“…24 Individual studies have had varied results (ISB and other blocks). Whereas some studies have concluded that perineural dexamethasone provides superior analgesia, 25,26 others have determined statistically significant but clinically insignificant differences, 27 and yet others have found no statistically significant differences between groups thereby concluding equivalence. 16,18,28 There are potential explanations for the contrasting results between these studies and our results identifying minimal differences.…”
Section: Discussionmentioning
confidence: 99%
“…Limited comparative efficacy among routes of administration has emerged. This appears most true for dexamethasone, which confers similar benefits to pain control and opioid use when administered via either modality [259,[327][328][329][330]333]. Although administering dexamethasone as a component of peripheral nerve blockade may avoid systemic side effects, perineural dexamethasone may have a local effect on nerve tissues that may be undesirable in some patient populations.…”
Section: Systemic Multimodal Adjunctsmentioning
confidence: 99%
“…78 potentially relevant articles are identi ed initially. Finally, ve RCTs that meet our inclusion criteria are included in the meta-analysis [10,12,13,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The doses of perineural or intravenous dexamethasone supplemented to interscalene block range from 1 mg to 5 mg. Among the ve studies included here, three studies report block duration [10,12,13], three studies report pain scores at 12 h [10,19,20], four studies report pain scores at 24 h [10,12,19,20], three studies report opioid consumption [10,12,13], and three studies report nausea/vomiting [10,19,20]. Jadad scores of the ve included studies vary from 3 to 5, and all ve studies are considered to have high quality according to quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation